기록관리표준에 관한 국내 연구동향 분석 - 허수진; 최상희; Sujin Heo; Sanghee Choi (Chŏngbo Kwalli Hakhoechi, 2023)
This study aimed to analyze and collect research trends of archival management standards in Korea. For this purpose, keywords from the titles, author keywords, and abstracts of papers related to records management standards were statistically analyzed to investigate the major keywords with high-frequency. Network analysis with high frequency keywords was also conducted to identify the subject areas of research in archival management standards. The analysis period is from 2000 to the present, and a total of 212 papers were collected from domestic academic paper search sites such as RISS and ScienceON. As a result of the analysis, from 2000 to 2010, OAIS for archive design, digital record preservation with OAIS, and analysis on ISO standards were mainly conducted in research areas. From 2011 until now, records management certification and ISAD(G)'s conversion to RiC emerged as new research areas. This study will be expected to be basic data to understand research trends in records management standards in Korea and to be a reference for research on records management standards studies. 이 연구는 국내 기록관리표준의 연구동향을 분석한 것으로 이를 위해 기록관리표준 관련 논문의 표제-주제어-초록의 키워드를 추출하여 상위빈도 키워드의 분석과 키워드 네트워크 분석을 수행하였다. 분석 대상 기간은 2000년부터 현재까지이며 RISS와 ScienceON 등의 국내 학술논문 검색사이트에서 총 212편의 논문을 수집하여 연구를 수행하였다. 분석 결과 2000~2010년까지는 아카이브 설계를 위한 OAIS의 연구, OAIS를 통한 디지털 기록 보존연구 ISO 표준의 분석 연구 등이 주로 진행되었고, 2011년 이후부터 지금까지는 기록경영인증, ISAD(G)의 RiC 전환 등의 연구가 진행되었음을 알 수 있었다. 이 연구는 기록관리표준 연구의 국내 연구동향을 분석함으로써 연구 흐름을 파악하는 기초자료로 활용되며, 기존 기록관리표준을 연구할 때 참고자료로 역할을 할 것으로 기대한다.